Chief Financial Officer Tenure and Financial Statement Comparability: Considering the Effect of Environment Uncertainty and Market Concentration - Tsai , Yuan-Tang; Wang , Teng-Shih (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study examines the relationship between chief financial officer (CFO) tenure and financial statement comparability, addressing a gap in the existing literature regarding how CFO leadership stability affects financial reporting quality, particularly within China’s unique institutional environment of capital markets. We find that longer CFO tenure significantly enhances financial statement comparability, utilising firm-level financial data from the Taiwan Economic Journal (TEJ) and CFO-specific data from the China Stock Market & Accounting Research Database (CSMAR) database covering the period from 2007 to 2018. Furthermore, our analysis reveals that CFO tenure moderates the adverse effects of environmental uncertainty on comparability, highlighting the role of experienced financial leadership in mitigating external risks. These findings contribute to the literature on executive characteristics and reporting quality by providing novel insights into the stabilising function of CFO tenure. From a policy perspective, our results underscore the importance of leadership continuity in corporate financial management, suggesting that regulators and corporate boards should recognise the value of retaining experienced CFOs to promote financial transparency and strengthen market confidence.